Does Ethical Context Affect the Ethically Related Judgment by the Observers of Earnings Management? - Feby Astrid Kesaulya; Weny Putri; Khairunnisa Khairunnisa (JASF: Journal of Accounting and Strategic Finance, 2019)
This research aims to empirically prove that there will be a difference in ethically related judgment by the observer of earnings management, primarily when they work in the company, which has a higher ethical context or value, and they know the moral agent personally. This research used experiment 2x2 between subjects to collect data by giving each respondent different treatments and scenarios. The different treatments to the respondents are the diverse workplaces with different ethical values and whether the respondents were related to the moral agent. The sample for this research is the students of Musi Charitas Catholic University from both accounting and management majors who have been taking specific courses, e.g., Business Ethics, Business and Management, and Management Control System, so that they can figure out the organizational structure and how earnings management happen. The final sample for this research is 67 respondents from both majors. The result of this research proves that there is no different ethically related judgment from each observer in each scenario, whether they come from the company with the high or low ethical context or whether they know the moral agent personally or not. The results indicate that ethical judgment is more affected by the ethical value from each person rather than organizational culture or egocentric bias.